Tufted wind-dispersed fagalean fruits, Pogonokarydion gen. nov., from the Upper Eocene Florissant Formation of Colorado, USA - Steven R. Manchester; Walter S Judd (Acta Palaeobotanica)
Wind-dispersed comose fruits from the Late Eocene of Florissant, Colorado, USA, are recognized as a new genus of fagalean affinity. Pogonokarydion crassulum (Cockerell) gen. et comb. nov. disseminules consist of an ellipsoidal to circular nut bearing longitudinal ribs, a persistent epigynous perianth, paired styles, and a prominent tuft of straight hairs arising from the base, which we infer to be homologous with an involucre. Prior assignments to Juncus (Juncaceae) and Fagopsis (Fagaceae) are rejected and we argue for a position within the Fagales, likely within, or close to, the Betulaceae. Pogonokarydion co-occurred in the Florissant flora with other fagalean genera, including some still living today, like Quercus and Carya , and others now extinct like Fagopsis and Asterocarpinus .